Prognostic significance of three‐tiered pathological classification for microvascular invasion in patients with combined hepatocellular‐cholangiocarcinoma following hepatic resection - Yijun Wu; Hongzhi Liu; Yifan Chen; Jianxing Zeng; Qizhen Huang; Jinyu Zhang; Yongyi Zeng; Jingfeng Liu (Cancer Medicine, 2023)
Abstract Background and Objectives Previous studies have reported that the microvascular invasion three‐tiered grading (MiVI‐TTG) scheme is a better prognostic predictor than the two‐tiered microvascular invasion (MiVI) grading scheme in hepatocellular carcinoma. This study aims to explore the prognostic significance of MiVI‐TTG in patients undergoing liver resection for combined hepatocellular‐cholangiocarcinoma (cHCC) and to explore the risk factors for MiVI in cHCC. Methods This research included 208 patients graded as M0, M1, or M2 using the MiVI‐TTG scheme. Predictive performance was assessed by Cox regression analysis, Kaplan–Meier curve with Log rank test, Harrell's c‐index, and time‐dependent areas under the receiver operating characteristic curve (tdAUC). The clinical utility of the two schemes was evaluated by decision cure analysis (DCA). The risk factors for MiVI were evaluated using logistic regression analysis. Results Among 208 cHCC patients, the proportions of M0, M1 and M2 were 38.9%, 36.5%, and 24.5%, respectively. Patients with severe MiVI status had worse recurrence‐free survival and overall survival (OS) based on Kaplan–Meier analysis. M1, M2, and MiVI‐positive were independent risk factors for early recurrence, while M2 and MiVI‐positive were associated with overall survival (OS). MiVI‐TTG had a larger c‐index, tdAUC, and net benefit rate than the two‐tiered MiVI grading scheme for predicting recurrence free survival and OS. AFP≥400 ng/ml was the independent risk factor for MiVI, and satellite nodules were independent risk factors for M2. Conclusions MiVI‐TTG has a greater prognostic value than the two‐tiered MiVI grading scheme in patients undergoing hepatic resection for cHCC.